Do Antimicrobial Peptides and Complement Collaborate in the Intestinal Mucosa? - Kopp, Zoë A.; Jain, Umang; Van Limbergen, Johan; Stadnyk, Andrew W. (Frontiers in Immunology, 2015)
It is well understood that multiple antimicrobial peptides (AMPs) are constitutively deployed by the epithelium to bolster the innate defenses along the entire length of the intestines. In addition to this constitutive/homeostatic production, AMPs may be inducible and levels changed during disease. In contrast to this level of knowledge on AMP sources and roles in the intestines, our understanding of the complement cascade in the healthy and diseased intestines is rudimentary. Epithelial cells make many complement proteins and there is compelling evidence that complement becomes activated in the lumen. With the common goal of defending the host against microbes, the opportunities for cross-talk between these two processes is great, both in terms of actions on the target microbes but also on regulating the synthesis and secretion of the alternate family of molecules. This possibility is beginning to become apparent with the finding that colonic epithelial cells possess anaphylatoxin receptors. There still remains much to be learned about the possible points of collaboration between AMPs and complement, for example whether there is reciprocal control over expression in the intestinal mucosa in homeostasis and restoring the balance following infection and inflammation.